Consumer's perception of price when they shop online - Ang, Kok Hou (2008)
Our research seeks to discover the impact of price on consumer's behaviour, the attributes of successful vendors as well as the types of products/services sellable in an online context. Our research sought to be a reference to online retailers or potential online retailers in formulating their pricing strategies.